Brand trust: a cross-national validation in Germany, India, and South Africa. Issue 1 (21st March 2016) - Hegner, Sabrina M.; Jevons, Colin
Abstract : Purpose: – Numerous studies have established the importance of brand trust for building long-term relationships with consumers. Nevertheless, there is confusion in the literature about how to measure trust in brands. Building on the studies of Li et al. (2008) and Li et al. (2015) who established brand trust as a second-order construct, this paper aims to demonstrate additional richness of the brand trust construct by adding further dimensions and extending the cultural background to Germany, India and South Africa. Design/methodology/approach: – Based on accepted scale development procedures, the authors have derived a parsimonious, reliable and valid scale to measure brand trust. Findings: – The resulting cross-national scales of brand trust demonstrate validity by offering a good fit and invariant measures across countries. The results show that overall brand trust is influenced by competence, predictability and benevolence/integrity. Practical implications: – Global communication technology means that brands are increasingly exposed internationally. To be successful in cross-cultural consumer-brand relationships, managers must build the skills to understand and deal with these cultural differences as well as understanding the fundamental aspects that do not differ across cultures. The model developed in this paper will be useful to both researchers and managers to get deeper insights into the trusting relationships their consumers have with their brand. Originality/value: – This cross-national study builds on recently published work and contributes to enriching brand trust understanding. Additionally, this research offers a validated, easily applicable, scale for measuring brand trust.